The impact of overweight and obesity in pregnancy: a 6 month retrospective study in Hospital Ampang, Malaysia - Khalid, S; Zulkhifli, ND; Narayan, G; Masri, MA; Shamsir Aris; Ganesalingam, M (Wiley-Blackwell, 2024)
Indexed by WOS